2005
DOI: 10.1103/physreva.71.032350
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement properties of multipartite entangled states under the influence of decoherence

Abstract: We investigate entanglement properties of multipartite states under the influence of decoherence. We show that the lifetime of (distillable) entanglement for GHZ-type superposition states decreases with the size of the system, while for a class of other states -namely all graph states with constant degree-the lifetime is independent of the system size. We show that these results are largely independent of the specific decoherence model and are in particular valid for all models which deal with individual coupl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
173
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(177 citation statements)
references
References 31 publications
4
173
0
Order By: Relevance
“…They show a strong violation of local reality and are shown to be robust against decoherence [25,26]. Much work has been done in trying to characterize the entanglement exhibited by these states, owing to their promising usefulness in Quantum information theory [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…They show a strong violation of local reality and are shown to be robust against decoherence [25,26]. Much work has been done in trying to characterize the entanglement exhibited by these states, owing to their promising usefulness in Quantum information theory [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…By "size" we mean either the number of particles or the number of internal degrees of freedom. However, Mermin [18] showed that the correlations found by n spacelike separated observers that share n qubits in a GHZ state violate a n-party (with n ≥ 3) BI by a factor that increases exponentially with n. An experimental verification of this exponentially growing nonlocality using GHZ states is difficult because it requires n spacelike separated measurements, and because n-party GHZ states' sensitivity to decoherence also grows with n [19].…”
mentioning
confidence: 99%
“…This interaction can cause the two-particle system to undergo decoherence [5,6,7], and the system will practically lose its quantum properties. The decay of Bell violation and entanglement measures of a decohering quantum system was studied recently in a number of works (see, e.g., [8,9,10,11,12]). In this paper we show that in the model of decoherence we use, there are two ways in which partial decoherence affects the ability of our two-particle system to violate the CHSH inequality.…”
mentioning
confidence: 99%
“…For state (11), the reduced density matrix of S has form (10), with r replaced by r * 1 r 2 . We see that the two-particle system with decoherence due to interactions of both particles is described by the same density matrix as the system in which only one particle interacts with its environment.…”
mentioning
confidence: 99%